Evaluation of onsite carbon footprint in landscape development stages based on life cycle assessment in Putrajaya, Malaysia - Badrul Hisham, Fara Diba (2018)
Carbon footprint has become very significant in our landscape development due to the large number of buildings and facilities. In order to increase carbon stock, carbon footprint from landscape lifecycle has to be reduced. Nevertheless, policies and plans that focus onsite carbon footprint in landscape development are still lacking. Therefore, this study presents the onsite carbon footprint evaluation of landscape development that was recently constructed in the Promenade Precinct 8, Putrajaya using Life Cycle Assessment. The Objectives of this study is to identify the stages, elements and attributes that increase onsite carbon footprint in landscape development stages; to assess the onsite carbon footprint in landscape development stages; to examine the contribution of stages, elements and attributes towards onsite carbon footprint and to propose an onsite carbon footprint reduction guideline in landscape development stages. Document analysis and field measurement were conducted, and data collected were analysed using SMART PLS (Partial Least Squares). The finding reveals that the construction stage produces the highest amount of carbon footprint with a value of 152884 kgCO2. As for the elements in landscape development, the highest amount comes from hardscape construction with a total of 58403 kgCO2. Lorry is the highest attribute that increases carbon footprint with a total amount of 99139 kgCO2. The guidelines focus on landscape development and would enhance the current assessment strategies in Malaysia. It can be implemented to offer a better understanding in mitigating the impact thus increasing carbon sequestration for improving the quality of life in the present and future developments.